DEPICTION OF YOGIC PRACTICES IN INDIAN ART - Pandey, Anjali (International Journal of Research -GRANTHAALAYAH, 2016)
Art has spectrum of expression that extends. Many sculptures and paintings convey the specific meaning and contents of Yoga. It occupied the distinct, one and only and unparalleled recognition for mental, physical moral and spiritual enhancement. The acceptance of yoga for ultimate achievement in life was inherent tradition "Yoga was one of the Fundamental doctrines devoted to the means to attain perfect health and mental poise" In the language of Indian art, the depiction of Yog Mudras, Asanas and Postures are employed as idioms to deepen the content and to enrich the meaning It is also the language of gesture which is unique, it works differently. The monastic abstraction, the eternal values the calmness of mind and the transcendent states of experience are perfectly reflected in Indian art work. In the cultural history of India, Yoga occupied the distinct, one and only and unparalleled recognition for mental, physical moral and spiritual enhancement. The acceptance of yoga for ultimate achievement in life was inherent tradition "Yoga was one of the Fundamental doctrine devoted to the means to attain perfect health and mental poise.